(untitled) (Journal of Environmental Science Studies, 2024)
This paper presents a comprehensive cost-benefit analysis of producing alternative phosphorus (P) fertilizers from recycled water treatment residuals (Fe-WTR) and cowshed effluents. The cost-benefit values of Fe-WTR are compared to the net costs of recycling P using a synthetic adsorbent (commonly used practice-layered double hydroxide, P-LDH) and the costs of commercial fertilizers. Dairy wastewater is used as a source of P. The cost of 1 ton P using the Fe-WTR process is €329. In contrast, synthetic adsorbents (P-LDH) incur significantly higher costs, amounting to €3329 per ton, underscoring the economic advantage of utilizing waste-derived materials. Adopting Fe-WTR fertilizer not only offers substantial cost savings by avoiding landfill fees (€40 per ton) and wastewater discharge fines (€500 per ton) but also reduces environmental impacts when compared to the use of commercial P fertilizers (non-recycled P). The Fe-WTR method mitigates eutrophication and pollution, presenting the dual benefit of cost-effectiveness and environmental protection, which exceeds the common P recycling practice (LDH). Our conclusions are based on production processes in Israel and compared to previous cost estimations at the world level, assessing the potential gain from such circular production of P globally. Recycling P from waste streams can be economically viable and environmentally preferable at small and large economic scales, supporting global sustainability goals.